2020
DOI: 10.5005/jp-journals-10083-0920
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Efficacy of Herbal and Non-herbal Toothpastes in Controlling Plaque and Gingivitis: A Review

Abstract: Background and aim: Dental plaque, a well-organized biofilm, is the established cause for gingivitis. Chronic gingivitis is the second most common disease of oral cavity which may progress to periodontitis. A mechanical plaque control method along with dentifrices is the most recommended method for plaque removal and controlling gingivitis. The aim of this review is to estimate and compare the effectiveness of herbal and non-herbal toothpastes in controlling plaque and gingivitis. Materials and methods: The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Suresh et al in his study observed that both herbal toothpaste and non-herbal toothpaste are equally powerful but no longer extra superior to fluoride toothpaste [ 23 ]. Nivethaprashanthi et al's study suggests that there is an increased interest in using herbal products [ 24 ]. Herbal toothpastes are as effective as non-herbal toothpastes in controlling plaque and gingivitis.…”
Section: Discussionmentioning
confidence: 99%
“…Suresh et al in his study observed that both herbal toothpaste and non-herbal toothpaste are equally powerful but no longer extra superior to fluoride toothpaste [ 23 ]. Nivethaprashanthi et al's study suggests that there is an increased interest in using herbal products [ 24 ]. Herbal toothpastes are as effective as non-herbal toothpastes in controlling plaque and gingivitis.…”
Section: Discussionmentioning
confidence: 99%